Beshie memes analyzing humor and gender portrayals in Megan Romero's memes - Delos Santos, Jessa John N. (2018)
Megan Romero is a local online celebrity who rose to fame due to his humorous, relatable, and self-made memes which he posts on Facebook. All the meme characters, as well as, the meme narratives are created by Romero himself. This study aimed to analyze how humor reinforces the gender portrayals in Megan Romero?s memes and to identify these said gender portrayals. This study is guided by Stuart Hall?s Representation and the Media and Mel Helitzer?s Elements of humor. A textual analysis was used to analyze seven memes that were purposively selected by the researcher. The results suggest that through the elements of humor, one can identify gender portrayals (through the element of realism) and gender expectations (through the element of hostility). As such, Romero?s memes were found to portray gender binaries, wherein the character that deviates such binaries are ridiculed or mocked through humor. It is notable, however, that this gender binarism found in Megan Romero?s memes tolerates certain breaches in gender roles like how it portrays men doing household chores.